The Role of Inclusive Education in Reducing Social Discrimination in Schools: Perspectives of Teachers and Students - Siti Nurhayati (LP3M KH Yazid Karimullah Institute, 2025)
Inclusive education that takes into account the diversity of students in all aspects, including disability, social background and culture, has an important role in reducing social discrimination in schools. This study aims to explore how inclusive education can reduce social discrimination in the school environment. The method used was qualitative with a case study approach involving in-depth interviews with 20 teachers and 50 students in two inclusive schools in Bandung and Surabaya. The results show that the implementation of inclusive education helps create a more tolerant atmosphere where students from different backgrounds can respect each other and work together. Teachers trained in inclusive education also showed better ability in handling differences and creating activities that encourage positive interactions between students. However, the challenge is the lack of understanding among some students and parents about the importance of inclusive education. This study suggests strengthening training for teachers and raising awareness about inclusive education through more intensive socialisation programs in schools.